2022
DOI: 10.15446/ing.investig.97702
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Optimization of Renewable Distrib-uted Generation: A Review

Abstract: Distributed energy resources, or distributed generation (DG), are the mainstay of modern power systems aiming towards green energy generation via the effective integration of renewable energy sources. DG involvement in traditional power systems comprises the enhancement of power quality parameters, the utilization of renewable sources, cost optimization, and stable and reliable energy generation. The advantages of such a revolutionary approach can be achieved with the optimal sizing and allocation of DG by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In [15], the authors presented a general literature review regarding the integration of renewable generation in electrical networks. They demonstrated that these technologies are the essential driver for improving the quality of the energy service, and they studied economic and atmospheric parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [15], the authors presented a general literature review regarding the integration of renewable generation in electrical networks. They demonstrated that these technologies are the essential driver for improving the quality of the energy service, and they studied economic and atmospheric parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brazilian Archives of Biology and Technology. Vol.67: e24230419, 2024 www.scielo.br/babt to solve the DG planning optimization problem [18,19]. The simulation parameters for the optimization technique are given in the table 1.…”
mentioning
confidence: 99%